Environmental and occupational health risks among agricultural workers living in a rural community near petroleum refinery and motorway in Skopje region - Jovanka Karadzinska-Bislimovska; Jordan Minov; Saso Stoleski; Dragan Mijakoski; Risteska-Kuc, Snežana; Milkovska, Snežana (Walter de Gruyter GmbH, 2010)
To assess health risks in agricultural workers associated with environmental exposure to pollutants released from a petroleum refinery and from traffic, we performed a cross-sectional study that included 119 randomly selected subjects divided in two groups. Group 1 included 60 agricultural workers living in a rural community near the petroleum refinery and a motorway overpass, whereas Group 2 consisted of 59 agricultural workers performing similar activities and living in a rural community with no exposure to industrial and traffic pollutants. Risk assessment included a questionnaire, blood pressure measurement, spirometry, laboratory tests, and toxicological analysis. The groups showed a similar prevalence of health problems, with exception of muscle pain in the extremities, headache, and fatigue, which were significantly more common in Group 1. Diastolic blood pressure was higher in Group 1, but not significantly (p=0.057). The same is true for blood carbon monoxide. Significantly higher in Group 1 were blood haemoglobin (p=0.001) and blood lead (p<0.001). Serum cholinesterase activity was similar in both groups. Our findings indicate the need of regular medical exams, ambient monitoring and environmental impact assessment in agricultural population in order to detect individuals at risk and to institute adequate preventive measures.
Keywords: blood pressure; environmental exposure; haemoglobin; rural environment; toxicological analysis